Revestimentos comestíveis à base de purê de manga e alginato de sódio para retenção de compostos voláteis em mangas minimamente processadas - Silva, Laiane Torres (Universidade Federal Rural do Semi-Árido, 2011)
The responses to mechanical damage caused by minimal processing can accelerate the loss of quality and modify the sensory attributes. Besides cooling, which is considered the main technique available to retard the undesirable effects of minimal processing, the use of barriers to O2/CO2 and water vapor can contribute in controlling senescence, maintaining the quality and extending the shelf-life. The objective of this study was to develop an edible coating based on mango puree and sodium alginate with minimal permeability to water vapor and the potential to form a thin gel layer around 'Tommy Atkins' minimally processed mango slices (MPM), capable of controlling gas exchange and water loss by the product, in order to maintain its quality and retain volatile compounds for a longer time. Eleven films were prepared, according to a central composite design with two variables, namely alginate concentration in the coatings and immersion time in calcium chloride. In a second part of the experiment, 'Tommy Atkins' mangoes, bought in the market, were washed, sanitized, peeled and cut into slices. MPM were immersed in the film forming solution for 30 seconds, and then in calcium chloride (1%) for 15 seconds, subsequently being disposed for 60 minutes on stainless steel sieve to drain. After this processing, 200g MMP were packed in polyethylene terephthalate trays with lids and stored under refrigeration (10 ± 2ºC) for six days. Every three days samples were collected to quantify the mass loss, pH, titratable acidity (TA), soluble solids (SS), SS/TA ratio, vitamin C, total sugars, polyphenoloxidase activity and volatile compounds. The experiment was conducted using CRD in 3 x 3 factorial design, with three treatments (control plus two coatings) in three storage times (1, 3, and 6 days). Data was subjected to analysis of variance; means of analysis of volatile compounds were compared by the method of Scott-Knott at 5% probability, and the average remaining analyses were compared by Tukey test at 5%. The edible films resulted in different water vapor permeabilities (WVP) as a function of the variables analyzed. The lowest WVP under the conditions used was 0.31 kPa mm-1 m-2, for 1% alginate and 15 seconds of immersion in CaCl2, and was therefore adopted as reference for the preparation of edible coatings. Analyses in gas chromatography-mass spectrometry revealed -3-carene as major constituent in mango aroma, and the same was used in this study as an indicator to assess the retention of volatile compounds of edible coatings. The mangoes coated with mango puree + sodium alginate (1%) exhibited the highest levels of this compound (64.47%). The edible coating (mango puree + sodium alginate) was efficient in maintaining the quality and retaining the -3-carene in mangos 'Tommy Atkins , stored at 10ºC for six days
Edible coatings of mango pulp and sodium alginate for retention of volatile compounds of minimally processed mangoes
Keywords: Mangifera indica; Minimal processing; sodium alginate; volatile compounds; Mangifera indica, processamento mínimo; alginato de sódio; compostos voláteis; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA